ANALISIS PENGENDALIAN MUTU SAMPLE UJI BETON UNTUK LANTAI PONDASI DI PROYEK ONE TOWER BSD CITY DENGAN MENGGUNAKAN SPC (STATISTICAL PROCESS CONTROL) - Jeffery Lucas; Lolom Evalita Hutabarat; Agnes Sri Mulyani (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2022)
ABSTRACTThe quality control system in construction projects is important to ensure that the work carried out meets quality standards in accordance with the established implementation time schedule. The larger the scale of a project has an impact on the complexity of the construction work that must be controlled so that a method is needed to control the quality of the work. In this study, the method used is the Statistical Process Control (SPC) method by taking a case study of the construction of One Tower BSD City which has a height of 22 floors and 3 basements. The research was conducted on the quality control of the tested concrete samples using Statistical Process Control (SPC). The results of the analysis of the quality of the concrete carried out on the foundation floor work with the concrete test sample taken from the inspection document data of the implementing contractor's production process. This research method uses descriptive qualitative in the form of analysis of compressive strength variability and slump test on concrete samples. The results showed that there was no deviation in the strength of the concrete based on the specified quality standard, namely f'c 35 MPa. There was a deviation in the results of the slump test of the concrete sample with 5 test results that were below the lower control limit, without affecting the results of the compressive strength of concrete samples.